2014
DOI: 10.15252/embj.201489455
|View full text |Cite
|
Sign up to set email alerts
|

BREX is a novel phage resistance system widespread in microbial genomes

Abstract: The perpetual arms race between bacteria and phage has resulted in the evolution of efficient resistance systems that protect bacteria from phage infection. Such systems, which include the CRISPR-Cas and restriction-modification systems, have proven to be invaluable in the biotechnology and dairy industries. Here, we report on a six-gene cassette in Bacillus cereus which, when integrated into the Bacillus subtilis genome, confers resistance to a broad range of phages, including both virulent and temperate ones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
493
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 445 publications
(503 citation statements)
references
References 37 publications
9
493
0
1
Order By: Relevance
“…Bioinformatics analyses predict the existence of many more immune mechanisms, often clustered together in defense islands (112). One such mechanism, coined bacteriophage exclusion (BREX), is widely distributed across bacteria and appears to share some mechanistic features with RM systems (261). We are starting to understand how all these different immune mechanisms work, but the next challenge is to examine when these mechanisms are favored over one another and how they are integrated during antiviral responses.…”
Section: Applications Conclusion and Outlookmentioning
confidence: 99%
“…Bioinformatics analyses predict the existence of many more immune mechanisms, often clustered together in defense islands (112). One such mechanism, coined bacteriophage exclusion (BREX), is widely distributed across bacteria and appears to share some mechanistic features with RM systems (261). We are starting to understand how all these different immune mechanisms work, but the next challenge is to examine when these mechanisms are favored over one another and how they are integrated during antiviral responses.…”
Section: Applications Conclusion and Outlookmentioning
confidence: 99%
“…lacusprofundi (Goldfarb et al, 2015), with a portion of the BREX genes contained on a~14 kb HIR present only in DL31 and Hrr. lacusprofundi, and FR coverage was low for the region containing the pglX gene (Supplementary Figure S7 Figure S7).…”
Section: Antarctic Haloarchaea-virus Interactions B Tschitschko Et Almentioning
confidence: 99%
“…lacusprofundi also potentially provide an additional mechanism for modulating the impact of viruses (Goldfarb et al, 2015), but much remains to be learned about the activity, viral specificity and dissemination of this system. Surveys of bacterial and archaeal genomes have shown that the pglX gene is prone to variation, including gene disruption, duplication and possible phase variation (Goldfarb et al, 2015). The metagenome FR data reveal that a high level of withinpopulation variation exists for pglX in Hrr.…”
Section: Antarctic Haloarchaea-virus Interactionsmentioning
confidence: 99%
See 2 more Smart Citations